Economic perspectives on adaptive reuse of heritage building as hotels in Georgetown, Penang / Amelina Zainudin and Lilawati Ab Wahab - Zainudin, Amelina; Ab Wahab, Lilawati (2019)
Modern design have threatened older and historical buildings to evolve. However, heritage buildings are better to keep and maintain the way it is due to the high building value it possessed. Some of the problems identified in this research are high cost of construction and uneconomic building return. The aim of this research is to study the economic perspectives of adaptive reuse in heritage buildings. The objectives are a) to identify adaptive reuse of heritage building as hotels, b) to determine the success factors and c) to study the rate of success of economic return on adaptive reuse heritage building as hotels in Georgetown, Penang. Data was collected by observations, questionnaires and interviews methods. These data were then analysed using SPSS (Version 24) Software. The results of this study will benefit any property investors whom wishes to adapt any heritage buildings into hotel. From this study, 30 heritage buildings was identified and adapted into hotels with interior design as the main success factor. With an average duratin of only 9 years to get back their capital return, hotel owners agreed that adaptive reuse is an investment that is worth to invest.